Effects of electrical stimulation of the rat vestibular labyrinth on c-Fos expression in the hippocampus. (11th June 2018) - Hitier, Martin; Sato, Go; Zhang, Yan-Feng; Besnard, Stephane; Smith, Paul F.
Highlights: Few studies have investigated electrical stimulation of the vestibular system on the hippocampus (HPC) in rodents. Here we investigated this in rats using c-Fos expression as a marker of activation. Significantly more animals exhibited increased positive c-Fos labelling in the dorsal HPC compared to sham controls, but not in the ventral HPC. Significantly more animals exhibited increased positive c-Fos labelling in the dorsal and ventral dentate gyrus compared to sham controls. Abstract: Several studies have demonstrated that electrical activation of the peripheral vestibular system can evoke field potential, multi-unit neuronal activity and acetylcholine release in the hippocampus (HPC). However, no study to date has employed the immediate early gene protein, c-Fos, to investigate the distribution of activation of cells in the HPC following electrical stimulation of the vestibular system. We found that vestibular stimulation increased the number of animals expressing c-Fos in the dorsal HPC compared to sham control rats (P ≤ 0.02), but not in the ventral HPC. c-Fos was also expressed in an increased number of animals in the dorsal dentate gyrus (DG) compared to sham control rats (P ≤ 0.0001), and to a lesser extent in the ventral DG (P ≤ 0.006). The results of this study show that activation of the vestibular system results in a differential increase in the expression of c-Fos across different regions of the HPC.